Why We Think We Can't Dance: Theory of Mind and Children's Desire to Perform. Issue 2 (9th November 2014) - Chaplin, Lan Nguyen; Norton, Michael I.
Abstract : Theory of mind (ToM) allows children to achieve success in the social world by understanding others' minds. A study with 3‐ to 12‐year‐olds, however, demonstrates that gains in ToM are linked to decreases in children's desire to engage in performative behaviors associated with health and well‐being, such as singing and dancing. One hundred and fifty‐nine middle‐class children from diverse backgrounds in a Northeastern U.S. metropolitan area completed the study in 2011. The development of ToM is associated with decreases in self‐esteem, which in turn predicts decreases in children's willingness to perform. This shift away from performance begins at age 4 (when ToM begins to develop), years before children enter puberty.